Multistructure Power Converter With H-Bridge Series Regulator Suitable for High-Current High-Precision-Pulsed Current Source - Penovi, Emiliano (2014)
This study presents a novel multistructure power converter capable of generating high current pulses with short rise and fall times, and high precision in the flat-top. The proposed topology is based on the use of three conversion structures operated with current, voltage and switching frequency ratings in line with the different requirements of each pulse stage. In order to achieve the required precision, a switched-mode compensation structure in series with the load is used. Though this structure must handle a high load current, it is designed to deviate most of the load current to an auxiliary inductor; thus reducing the semiconductor devices requirements. Moreover, the use of this compensation strategy results in a first-order model of the circuit, which leads to an oscillation-free response during structures interconnection. This feature minimizes the required flat-top time, which in turn decreases the power losses on the load. Experimental results based on a scaled-down laboratory prototype validate the capability of the proposed topology to produce current pulses according to the specifications of high-precision applications.